Central nitrergic system regulation of neuroendocrine secretion, fluid intake and blood pressure induced by angiotensin-II - Reis, Wagner L. [UNESP] (2010)
Background: Nitric oxide (NO) synthesis has been described in several circumventricular and hypothalamic structures in the central nervous system that are implicated in mediating central angiotensin-II (ANG-II) actions during water deprivation and hypovolemia. Neuroendocrine and cardiovascular responses, drinking behavior, and urinary excretions were examined following central angiotensinergic stimulation in awake freely-moving rats pretreated with intracerebroventricular injections of N omega-nitro-L-arginine methyl ester (L-NAME, 40 mu g), an inhibitor of NO synthase, and L-arginine (20 ug), a precursor of NO.Results: Injections of L-NAME or ANG-II produced an increase in plasma vasopressin (VP), oxytocin (OT) and atrial natriuretic peptide (ANP) levels, an increase in water and sodium intake, mean arterial blood pressure and sodium excretion, and a reduction of urinary volume. L-NAME pretreatment enhanced the ANG-II response, while L-arginine attenuated VP and OT release, thirst, appetite for sodium, antidiuresis, and natriuresis, as well as pressor responses induced by ANG-II.Discussion and conclusion: Thus, the central nitrergic system participates in the angiotensinergic responses evoked by water deprivation and hypovolemia to refrain neurohypophysial secretion, hydromineral balance, and blood pressure homeostasis.